Association between cannabis and the eyelids: A comprehensive review. (6th December 2019) - Nguyen, Anne X.; Wu, Albert Y.
Abstract: Cannabis is the most consumed illicit drug worldwide. As more countries consider bills that would legalize adult use of cannabis, health care providers, including eye care professionals (ophthalmologists, optometrists), will need to recognize ocular effects of cannabis consumption in patients. There are only 20 studies on the eyelid effects of cannabis usage as a medical treatment or a recreational drug. These include ptosis induction, an "eyelid tremor" appearance and blepharospasm attenuation. Six articles describe how adequately dosed cannabis regimens could be promising medical treatments for blepharospasm induced by psychogenic factors. Fourteen articles report eyelid tremors in intoxicated drivers and ptosis as a secondary effect in cannabinoid animal experimental models. The exact mechanism of cannabinoids connecting cannabis to the eyelids is unclear. Further studies should be conducted to better understand the cannabinoid system in relation to the eyelid and eventually develop new, effective and safe therapeutic targets derived from cannabis.